2020
DOI: 10.31234/osf.io/eahjd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Violations of expectation trigger infants to search for explanations

Abstract: Infants look longer and explore more following violations-of-expectation, but the reasons for these surprise-induced behaviors are unclear. One possibility is that expectancy violations increase arousal generally, thereby increasing infants’ post-surprise activity. Another possibility is that infants’ exploration reflects the search for an explanation for the surprising event. We tested these alternatives in three experiments. First in Experiment 1 we confirmed that seeing an object violate expectations (by pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
2
17
1
Order By: Relevance
“…In Experiment 1a, we found that infants looked longer at an event in which the principle of object support was violated, compared to an event that did not violate object support. However, the same infants showed no evidence of detecting a violation of object solidity-a result that contrasts with in-lab studies (Perez & Feigenson, 2020Spelke et al, 1992). In Experiment 1b, we found that infants' word learning was enhanced following a violation of object support, compared to following a nearly identical event that did not culminate in a violation.…”
Section: Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…In Experiment 1a, we found that infants looked longer at an event in which the principle of object support was violated, compared to an event that did not violate object support. However, the same infants showed no evidence of detecting a violation of object solidity-a result that contrasts with in-lab studies (Perez & Feigenson, 2020Spelke et al, 1992). In Experiment 1b, we found that infants' word learning was enhanced following a violation of object support, compared to following a nearly identical event that did not culminate in a violation.…”
Section: Resultscontrasting
confidence: 88%
“…All analyses were planned ahead of data collection and were modeled after previous experiments (see Perez & Feigenson, 2020;Stahl & Feigenson, 2015). We examined infants' looking times using a repeated measures ANOVA with Outcome Type as a within-subject factor (Unexpected vs. Expected), and Outcome Event Pairing (a Solidity event with an Unexpected Outcome paired with a Support event with an Expected Outcome, or a Solidity event with an Expected Outcome paired with a Support event with an Unexpected Outcome) and Outcome Order (Unexpected Outcome or Expected Outcome first) as between-subject factors.…”
Section: Resultsmentioning
confidence: 99%
“…These behaviors are tuned to whether an event needs to be explained: If an explanation for the violation is provided (e.g. the solid wall had a hole through the object could pass), infants no longer selectively explore that object (Perez & Feigenson 2020). These findings underscore how information gained from infants' looking at informative events calibrates subsequent exploration and learning (reviewed in Stahl & Feigenson 2018).…”
Section: Behavioral Evidencementioning
confidence: 99%
“…surprise-induced exploration is abolished if the infants are provided with an explanation about why the object was behaving in a surprising manner (Perez & Feigenson, 2020).…”
Section: /55mentioning
confidence: 99%